Vaccinotherapy in renal cell carcinoma - Kowalczyk, Dariusz W. (Contemporary Oncology/Współczesna Onkologia, 2007)
Renal cell carcinoma is resistant to classical radiotherapy or chemotherapy. On the other hand these tumors seem to be immunogenic which make them potentially susceptible to immunotherapeutic approaches including anti-cancer vaccines. This article presents an analysis of recent publications on vaccine based treatments of renal cell carcinoma. Through Medline search 41 clinical trials were identified involving 1094 patients. Tested vaccines were composed of tumor cells, tumor lysates, dendritic cells, peptides or heat shock proteins. Clinical response data were presented for 657 patients with advanced (stage IV) cancer. Objective response was observed in about 27.4% of these patients: 20 patients showed complete response (CR) (3.0%), 36 partial response (PR) (5.5%), 10 mixed response (MR) (1.5%) and 114 had stable disease (SD) (17.4%). It appears that active, vaccine based immunotherapy may induce anti-tumor immune reaction in selected group of patients leading to moderate clinical responses.